Toward a sex‐specific relationship between muscle strength and appendicular lean body mass index?. Issue 2 (7th February 2013) - Barbat-Artigas, Sébastien; Plouffe, Stéphanie; Pion, Charlotte H.; Aubertin-Leheudre, Mylène
Abstract : Background: In spite of some dissociation between muscle mass and strength, muscle strength is often used as a proxy to identify individuals with low muscle mass (sarcopenia). Thus, the aim of the present study was to investigate the relationship between muscle strength and the appendicular lean body mass index (app LBMI). Methods: One hundred and five individuals were recruited. Knee extension and handgrip strength were measured. Body composition was assessed by DXA. App LBMI was calculated as appendicular lean body mass divided by height squared. Results: At le level of the entire cohort, both handgrip ( r  = 0.73; p  < 0.001) and knee extension strength ( r  = 0.57; p  < 0.001) were associated with app LBMI. However, in women, knee extension strength ( r  = 0.32; p  < 0.05) but not handgrip strength ( r  = 0.14; p  = 0.35) was associated with app LBMI; while in men, handgrip strength ( r  = 0.43; p  < 0.01) but not knee extension strength ( r  = 0.27; p  = 0.09) was associated with app LBMI. Conclusions: Muscle strength appears to be associated with lean body mass; however, handgrip strength may be preferentially used in men and knee extension strength in women to detect sarcopenic individuals. Future larger studies are now needed to confirm our findings and their clinical relevance.